Diagnostics and susceptibility testing in Aspergillus. (February 2016) - Bernal-Martínez, Leticia; Alastruey-Izquierdo, Ana; Cuenca-Estrella, Manuel
Invasive aspergillosis is a major cause of morbidity and mortality in immunosuppressed patients. Early diagnosis and correct antifungal treatment have a direct impact on patient survival. A number of newer diagnostic procedures have been developed as alternatives to conventional microbiological methods. The detection of fungal components, largely antigens and DNA, are used in clinical laboratories to diagnose invasive aspergillosis. Other rapid diagnostic tests have been recently developed with promising results. However, antifungal resistance is becoming an emerging problem. The detection of this resistance is important to administer the proper antifungal agent. This text reviews the novelties on new diagnostics Aspergillus spp. procedures. Intrinsic antifungal resistance and mechanisms of secondary resistance to triazoles in A. fumigatus are also reviewed.